Preparation method of angular aluminum nitride large-particle powder
Through the combustion synthesis method of aluminum powder, aluminum nitride powder and sintering additives, a large-grain aluminum nitride powder was prepared, which solved the problems of complex and high cost of preparation of large-grain aluminum nitride powder, realized the application of high thermal conductivity fillers, and improved the heat dissipation performance of electronic devices.
Patent Information
- Application Number
- CN202510509726.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-22
- Publication Date
- 2025-07-18
AI Technical Summary
The existing large-particle aluminum nitride thermal filler powder preparation process is complex and costly, which limits its application in the field of thermal filler.
Aluminum nitride ceramics are synthesized by mixing aluminum powder, aluminum nitride powder and sintering additives by combustion under high-pressure nitrogen atmosphere. After crushing and sieving, a large angular aluminum nitride powder was obtained. The combustion reaction exothermic was used to achieve one-step synthesis and sintering.
The preparation process is simplified and the cost is reduced. The prepared large-grain powder of angular aluminum nitride can be used as a high thermal conductivity filler, solving the heat dissipation problem of electronic devices.
Smart Images

Figure CN120329049A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of ceramic materials, and particularly to a method for preparing angular aluminum nitride large particle powder. Background Art
[0002] With the development of integrated circuits towards high integration and miniaturization, the power consumption and heat generation of chips have increased sharply, and the resulting heat dissipation problem has attracted much attention. Composite materials such as potting adhesives, plastic encapsulants, and thermal interface materials composed of organic matrices and thermal conductive fillers are important electronic packaging materials and play a crucial role in the efficient heat dissipation of electronic devices and components. In such composite materials, the matrix is usually resin, which has good ductility and plasticity but low thermal conductivity. The thermal conductivity of the composite material mainly depends on the thermal conductive filler.
[0003] Aluminum nitride (AlN) thermal conductive filler, with a theoretical thermal conductivity as high as 320 W / m·K, has excellent properties such as a small thermal expansion coefficient, good insulation performance, and low dielectric constant, and is a key material for solving the heat dissipation problem. To improve the thermal conductivity of thermal conductive composite materials, fillers of different particle sizes are usually used for particle grading to construct a thermal conductive network within the composite material. Aluminum nitride powders of different particle sizes are the key to preparing high thermal conductivity composite materials. Currently, aluminum nitride powders with a particle size range of 0.5 - 20 μm can be directly synthesized by methods such as carbothermal reduction nitridation, direct nitridation, and combustion synthesis. For aluminum nitride thermal conductive filler powders with larger particle sizes (20 - 200 μm), they are prepared by granulation and sintering methods. Due to the intrinsic properties of aluminum nitride such as easy hydration and high sintering temperature, the preparation cost of large particle aluminum nitride filler powders remains high, severely limiting its application in the field of thermal conductive fillers.
[0004] The present invention discloses a method for preparing angular aluminum nitride large particle powder, which utilizes the exothermic combustion reaction of aluminum powder and nitrogen to achieve one-step synthesis and sintering of aluminum nitride, and obtains angular aluminum nitride large particle powder after crushing and screening. This method has the characteristics of simple process and low preparation cost. The prepared angular aluminum nitride large particle powder can be used as a high thermal conductivity filler for electronic packaging. Summary of the Invention
[0005] The present invention discloses a method for preparing angular aluminum nitride large particle powder, which solves the technical problems of complex preparation process and high cost of existing large particle aluminum nitride thermal conductive filler powders.
[0006] To achieve the above object, the present invention adopts the following technical solutions: A preparation method of angular aluminum nitride large particle powder, characterized in that the raw materials include aluminum powder, aluminum nitride powder and sintering aids. After weighing, mixing and pressing into shape according to the ratio, the raw material green body is subjected to combustion synthesis in a high-pressure nitrogen atmosphere to obtain aluminum nitride ceramics, and 20-200 μm angular aluminum nitride large particle powder is obtained after crushing and screening.
[0007] Preferably, for the raw material ratio, by mass percentage: aluminum powder is 25%-35%, aluminum nitride powder is 63%-70%, and sintering aids are 2%-5%, and the sum of the masses of all raw materials is 100%.
[0008] Preferably, the particle size of the aluminum powder is 5-25 μm, and the particle size of the aluminum nitride powder is 1-3 μm.
[0009] Preferably, the sintering aid is Y2O3, and its particle size is 0.1-0.5 μm.
[0010] Preferably, the porosity of the raw material green body is 40%-45%.
[0011] Preferably, the nitrogen atmosphere pressure range is 1 MPa-5 MPa.
[0012] Preferably, the porosity of the aluminum nitride ceramic is 15%-20%.
[0013] Unless otherwise specified, any range recorded in the present invention includes the end values and any values between the end values, as well as any sub-ranges formed by any values between the end values or the end values.
[0014] The present invention utilizes the heat released by the combustion reaction of aluminum powder and nitrogen to realize the one-step synthesis and sintering of aluminum nitride. Through the regulation of a small amount of sintering aids and atmosphere pressure, the synthesis and sintering of aluminum nitride are promoted, the strength and density of the product are improved, and 20-200 μm angular aluminum nitride large particle powder is obtained after crushing and screening; this preparation method can significantly reduce the preparation cost. The prepared angular aluminum nitride large particle powder can be used as a high thermal conductivity filler in the field of electronic packaging to solve the heat dissipation problem of electronic devices. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] FIG. 1. XRD pattern of the synthesis product in Example 1; FIG. 2. SEM photograph of the synthesis product in Example 1. DETAILED DESCRIPTION OF THE INVENTION
[0016] Example 1 Aluminum powder with a particle size of 5 μm, aluminum nitride powder with a particle size of 3 μm, and yttrium oxide powder with a particle size of 0.5 μm were selected as raw materials. According to the mass percentage Al:AlN:Y2O3 = 25%:70%:5%, the raw materials were weighed and mixed, and then pressed to obtain a green body with a porosity of 45%. The green body was placed in a combustion synthesis device, evacuated, and then nitrogen gas was introduced at a pressure of 5 MPa. Subsequently, a combustion reaction was induced by an energized tungsten coil. After cooling, aluminum nitride ceramics were obtained, and their porosity was measured to be 20%. After crushing and screening, angular aluminum nitride large particle powders with a particle size of 20 - 200 μm were obtained. An appropriate amount of the sample was subjected to XRD testing, as shown in the appendix Figure 1 As shown, the results indicate that the main phase of the product is AlN, and it also contains a small amount of Y4Al2O9 and YAlO3, and there is no residual unreacted Al. Samples with different particle sizes after screening were subjected to SEM characterization, as shown in the appendix Figure 2 As shown, the AlN particles are angular in shape and the particle surfaces are dense.
[0017] Example 2 Aluminum powder with a particle size of 10 μm, aluminum nitride powder with a particle size of 2 μm, and yttrium oxide powder with a particle size of 0.4 μm were selected as raw materials. According to the mass percentage Al:AlN:Y2O3 = 28%:68%:4%, the raw materials were weighed and mixed, and then pressed to obtain a green body with a porosity of 44%. The green body was placed in a combustion synthesis device, evacuated, and then nitrogen gas was introduced at a pressure of 4 MPa. Subsequently, a combustion reaction was induced by an energized tungsten coil. After cooling, aluminum nitride ceramics were obtained, and their porosity was measured to be 18%. After crushing and screening, angular aluminum nitride large particle powders with a particle size of 20 - 200 μm were obtained. An appropriate amount of the sample was subjected to XRD testing, and the results indicate that the main phase of the product is AlN, and it also contains a small amount of Y4Al2O9 and YAlO3, and there is no residual unreacted Al. Samples with different particle sizes after screening were subjected to SEM characterization, and the AlN particles are angular in shape and the particle surfaces are dense.
[0018] Example 3 Aluminum powder with a particle size of 15 μm, aluminum nitride powder with a particle size of 2 μm, and yttrium oxide powder with a particle size of 0.3 μm were selected as raw materials. According to the mass percentage Al:AlN:Y2O3 = 30%:67%:3%, the raw materials were weighed and mixed, and then pressed to obtain a green body with a porosity of 43%. The green body was placed in a combustion synthesis device, evacuated, and then nitrogen gas was introduced at a pressure of 3 MPa. Subsequently, a combustion reaction was induced by an energized tungsten coil. After cooling, aluminum nitride ceramics were obtained, and their porosity was measured to be 17%. After crushing and screening, angular aluminum nitride large particle powders with a particle size of 20 - 200 μm were obtained. An appropriate amount of the sample was subjected to XRD testing, and the results indicate that the main phase of the product is AlN, and it also contains a small amount of Y4Al2O9, and there is no residual unreacted Al. Samples with different particle sizes after screening were subjected to SEM characterization, and the AlN particles are angular in shape and the particle surfaces are dense.
[0019] Example 4 Aluminum powder with a particle size of 20 μm, aluminum nitride powder with a particle size of 1 μm, and yttrium oxide powder with a particle size of 0.2 μm were selected as raw materials. According to the mass percentage Al:AlN:Y2O3 = 32%:66%:2%, after weighing and mixing the raw materials, a green body with a porosity of 42% was pressed, and then placed in a combustion synthesis device. After evacuating, nitrogen gas with a pressure of 1 MPa was introduced. Subsequently, an electric current was passed through a tungsten coil to induce a combustion reaction. After cooling, aluminum nitride ceramics were obtained, and its porosity was measured to be 16%. After crushing and screening, angular aluminum nitride large particle powders with a particle size of 20 - 200 μm were obtained. An appropriate amount of the sample was taken for XRD testing. The results showed that the main phase of the product was AlN, and it also contained a small amount of Y4Al2O9, and there was no residual unreacted Al. Samples with different particle sizes after screening were taken for SEM characterization. The AlN particles were angular in shape, and the particle surface was dense.
[0020] Example 5 Aluminum powder with a particle size of 25 μm, aluminum nitride powder with a particle size of 1 μm, and yttrium oxide powder with a particle size of 0.1 μm were selected as raw materials. According to the mass percentage Al:AlN:Y2O3 = 35%:63%:2%, after weighing and mixing the raw materials, a green body with a porosity of 40% was pressed, and then placed in a combustion synthesis device. After evacuating, nitrogen gas with a pressure of 1 MPa was introduced. Subsequently, an electric current was passed through a tungsten coil to induce a combustion reaction. After cooling, aluminum nitride ceramics were obtained, and its porosity was measured to be 15%. After crushing and screening, angular aluminum nitride large particle powders with a particle size of 20 - 200 μm were obtained. An appropriate amount of the sample was taken for XRD testing. The results showed that the main phase of the product was AlN, and it also contained a small amount of Y2Al4O9, and there was no residual unreacted Al. Samples with different particle sizes after screening were taken for SEM characterization. The AlN particles were angular in shape, and the particle surface was dense.
[0021] Some examples To examine the influence of the raw material ratio on the phase and porosity of the synthesized product, that is, the method steps and conditions were the same as in Example 1, except that the raw material ratio was different. The results are shown in the following table.
[0022] Table 1 Influence of different ratios on the phase and porosity of the product Number Al powder (%) AlN powder (%) <![CDATA[Y2O3 (%)]]> Product phase Product porosity (%) 1 20% 75% 5 Unreacted — 2 40% 55% 5 <![CDATA[AlN, Y2Al4O9, YAlO3, Al]]> 13 3 25% 75% 0 AlN 34 4 25% 74% 1 AlN 28 5 25% 69% 6 <![CDATA[AlN, Y2Al4O9, Y2O3]]> 19 Conclusion: When the ratio of Al powder is 20%, the combustion synthesis reaction cannot proceed, and the green body does not react; when the ratio of Al powder reaches 40%, there is residual unreacted aluminum in the product; when Y2O3 is not added, the porosity of the synthesized aluminum nitride is 35%, the particle strength is low, and it is easily broken into <20 μm fine powder, and it is difficult to obtain angular large particles; When the ratio of Y2O3 is 1%, the porosity of the synthesized aluminum nitride is low, and it is still easily broken into <20 μm fine powder during crushing; when the ratio of Y2O3 is 6%, the Y2O3 phase appears in the product.
[0023] Some examples To examine the effects of raw material particle size on the phase and porosity of the synthesized product, i.e., the method steps and conditions are the same as in Example 5, except that the raw material particle sizes are different, and the results are as shown in the following table.
[0024] Table 1 Effects of different raw material particle sizes on the phase and porosity of the product Number Al powder (μm) AlN powder (μm) <![CDATA[Y2O3 (μm)]]> Product phase Product porosity (%) 1 5 1 0.1 <![CDATA[AlN, Y2Al4O9, Al]]> 23 2 15 1 0.1 <![CDATA[AlN, Y2Al4O9, Al]]> 20 3 20 1 0.1 <![CDATA[AlN, Y2Al4O9]]> 18 4 25 2 0.1 <![CDATA[AlN, Y2Al4O9]]> 17 5 25 3 0.1 <![CDATA[AlN, Y2Al4O9]]> 19 6 25 5 0.1 <![CDATA[AlN, Y2Al4O9]]> 26 7 25 1 0.3 <![CDATA[AlN, Y2Al4O9]]> 16 8 25 1 0.5 <![CDATA[AlN, Y2Al4O9]]> 18 9 25 1 1 <![CDATA[AlN, Y2Al4O9]]> 24 Conclusion: When the Al powder ratio is 35%, using raw materials with smaller particle sizes, there is residual aluminum in the product, and the porosity of the product increases; the porosity of the product decreases with the increase in the particle sizes of aluminum nitride and yttrium oxide.
[0025] Some embodiments To examine the effects of nitrogen pressure on the phase and porosity of the synthesized product, i.e., the method steps and conditions are the same as in Example 1, except that only the nitrogen pressure is different, and the results are as shown in the following table.
[0026] Table 2 Effects of different pressures on the phase and porosity of the product Number Nitrogen pressure MPa Product phase Product porosity (%) 1 0.5 <![CDATA[AlN, Y2Al4O9, YAlO3]]> 27 2 1 <![CDATA[AlN, Y2Al4O9, YAlO3]]> 25 3 3 <![CDATA[AlN, Y2Al4O9, YAlO3]]> 23 4 5 <![CDATA[AlN, Y2Al4O9, YAlO3]]> 20 5 7 <![CDATA[AlN, Y2Al4O9, YAlO3]]> 20 Conclusion: Nitrogen pressure has no effect on the phase of the product; the porosity of the product decreases with the increase in pressure. When the nitrogen pressure is higher than 5 MPa, the porosity of the product no longer continues to decrease. A low porosity is beneficial to increasing the strength of the synthesized aluminum nitride ceramic, making it less likely to become fine powder during crushing, and enhancing the thermal conductivity of large particle powders.
[0027] Some embodiments To examine the effects of the porosity of the raw material green body on the phase and porosity of the synthesized product, i.e., the method steps and conditions are the same as in Example 1, except that only the porosity of the raw material green body is different, and the results are as shown in the following table.
[0028] Table 3 Effects of different porosities of the raw material green body on the phase and porosity of the product Number Raw material green body porosity (%) Product phase Product porosity (%) 1 60 <![CDATA[AlN, Y2Al4O9, YAlO3]]> 43 2 55 <![CDATA[AlN, Y2Al4O9, YAlO3]]> 38 3 50 <![CDATA[AlN, Y2Al4O9, YAlO3]]> 27 4 45 <![CDATA[AlN, Y2Al4O9, YAlO3]]> 20 5 40 <![CDATA[AlN, Y2Al4O9, YAlO3]]> 18 Conclusion: The porosity of the raw material green body has no effect on the phase of the product; the porosity of the product decreases with the decrease in the porosity of the raw material green body. It is difficult to obtain a raw material green body with a porosity lower than 40% by conventional pressing methods.
[0029] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, rather than limitations on the implementation manners of the present invention. For those of ordinary skill in the art, other different forms of changes or modifications can be made based on the above description. It is impossible to enumerate all the implementation manners here. Any obvious changes or modifications derived from the technical solutions of the present invention still fall within the protection scope of the present invention.
Claims
1. A method for preparing large-grained angular aluminum nitride powder, comprising the following steps: After weighing, mixing, and compacting the raw materials including aluminum powder, aluminum nitride powder, and sintering aids according to the ratio, the raw material green body is subjected to combustion synthesis in a high-pressure nitrogen atmosphere to obtain aluminum nitride ceramics, and 20-200 μm angular aluminum nitride large particle powder is obtained after crushing and screening.
2. The method according to claim 1, wherein For the described raw material ratio, by mass percentage: aluminum powder is 25%-35%, aluminum nitride powder is 63%-70%, and sintering aids are 2%-5%, and the sum of the masses of all raw materials is 100%.
3. The method according to claim 1, characterized in that, The particle size of the aluminum powder is 5-25 μm, and the particle size of the aluminum nitride powder is 1-3 μm.
4. The method according to claim 1, wherein The sintering aid is Y2O3, and its particle size is 0.1-0.5 μm.
5. The method according to claim 1, characterized in that, The porosity of the raw material green body is 40%-45%.
6. The method according to claim 1, characterized in that, The pressure range of the nitrogen atmosphere is 1 MPa-5 MPa.
7. The method according to claim 1, characterized in that, The porosity of the aluminum nitride ceramics is 15%-20%.
Citation Information
Cited By
Preparation method of high-purity aluminum nitride single crystal powder
CN121321202A
Preparation method of high-purity aluminum nitride single crystal powder
CN121321202B